Zakat as a Fiscal Policy Tool in the Perspective of Islamic Economics - Judijanto, Loso; Jainudin, Jainudin; Ngampo, Hendrongi; Muhammadong, Muhammadong (West Science Islamic Studies, 2025)
This study investigates the potential of zakat as a fiscal policy tool within the framework of Islamic economics through a systematic literature analysis of 15 SCOPUS-indexed academic publications. The analysis reveals that zakat serves as a powerful mechanism for wealth redistribution, poverty alleviation, and macroeconomic stabilization. When institutionalized effectively, zakat complements conventional fiscal tools by funding public welfare programs and supporting economic equity. The reviewed literature underscores that countries like Malaysia and Indonesia have begun integrating zakat into national strategies, demonstrating its fiscal relevance. However, significant challenges remain, including fragmented governance, limited transparency, and the absence of integration with formal public finance systems. The study concludes that mainstreaming zakat into national fiscal policy frameworks—while respecting its religious character—can enhance economic justice and promote sustainable development in Muslim-majority societies.